SPATIAL AND TEMPORAL DISTRIBUTION OF PORE THROATS IN RESERVOIR SANDSTONE: IMPLICATION TO PERMEABILITY VARIATION IN WEST BARAM DELTA, MALAYSIA - Yusuf, Ishaq (FUDMA JOURNAL OF SCIENCES, 2023)
This paper attempts to quantify pore throats distribution towards more effective approach to permeability prediction. The mercury inoculation capillary pressure (MICP) is used to calculate pore throat diameters, and porosity-permeability system (POROPERM) validates effect of pore throats diameters on permeability variations from core plugs. Results reveal three major classes of pore throats diameters (micropore, mesopore and macropore) from five identified pore throat types. It indicates also that the abundance of mesopore and macropore throats above 30% in upper section (1475 m – 1480 m) of Siwa well increases permeability above 990 mD, an increase in micropore throats in middle unit (2106 m – 2114 m) of BK-102 well vary permeability from 495 mD to 600 mD. Whereas, in the TK well, permeability is moderate lower between 230 mD to 670 mD due to abundance of macropore throats in groundmass of the fine to very fine-grained sandstones. In WL well, at depth from 1720 m to 1850 m, permeability is moderate higher varying between 120 mD to 945 mD attributed to abundance mesopore and macropore throats presence in coarse friable and medium grained sandstones within stratigraphic succession. The results also indicates that increase in percentage composition of mesopore and macropore throats above 20% holds potential increase in permeability, and conversely increase in micropore throats type 1-3 disrupts or lowers permeability. The understanding of spatial and temporal distribution of pore throats in wells, could improve accurate prediction permeability and hydraulic flow units in reservoirs